Simultaneous maxillomandibular distraction osteogenesis in hemifacial microsomia: Report of 7 cases - Divya Mehrotra; Debraj Howladar; Dichen P. Bhutia (Elsevier, 2017)
Introduction: The goal in treating Hemifacial microsomia (HFM) is to improve facial symmetry, allow functional jaw movement, obtain stable occlusion, and achieve patient satisfaction. This study was planned with an aim to assess the outcome of simultaneous maxillomandibular distraction osteogenesis in hemifacial microsomia. Material & methods: Seven patients with hemifacial microsomia were included in this study and demographic data was obtained. Simultaneous maxillo-mandibular distraction was planned for correction of maxillary cant, vertical ramal lengthening and midline, by performing unilateral mandibular osteotomy in ramus and distractor fixation, a Le Fort I osteotomy, with fixation at contralateral zygomatic buttress and intermaxillary elastics. Derriford Appearance Scale was used to measure individual responses to address problems of appearance. Results: 6 males and 1 female, with age range 18-26 years, mean 22.14 were included in the study. Maxillary occlusal cant varied from 4-16°, mean 9.85° and distraction achieved ranged from 12-19 mm, mean 15.57. Preoperatively DAS score ranged from 42-61, mean 51.7 and improved to 10-27, mean 18.4. 100% success was achieved in 5 cases, while other two showed 96% and 99% success. Conclusion: Simultaneous maxillomandibular distraction osteogenesis improves facial esthetics and obviates the need for postoperative orthodontics, minimizing the treatment period.